Effect of a training module on the beliefs of student teachers with regard to repetition. A qualitative study at the University of Geneva - Boraita, Fanny (Swiss Journal of Educational Research, 2018)
This study aims to analyze the evolution of the beliefs about grade repetition of 11 pre-service teachers during a training sequence, alternating theoretical courses and periods of participatory observation of classes in ordinary and specialized education. This training module focuses on the learning difficulties of students in school situations and on ways of intervention to promote their progress in learning. These 11 pre-service teachers responded to two interviews, one before the training sequence and the other one after, concerning their beliefs about grade repetition, students’ difficulties and ways to cope with these difficulties. Changes and/or developments in beliefs are observed in most of the pre-service teachers. These are attained by them through theoretical courses and, specifically, to the fact that during these courses, they could test their own beliefs against research results. It also appears that changes in beliefs about grade repetition are accompanied by developments in other domains: learning, equality and justice, teaching differentiation. This article concludes with a discussion on the stability of changes and evolutions observed.